Enhanced Oxygen Supply Improves Islet Viability in a New Bioartificial Pancreas. Issue 8 (August 2013) - Barkai, Uriel; Weir, Gordon C.; Colton, Clark K.; Ludwig, Barbara; Bornstein, Stefan R.; Brendel, Mathias D.; Neufeld, Tova; Bremer, Chezi; Leon, Assaf; Evron, Yoav; Yavriyants, Karina; Azarov, Dimitri; et al.
The current epidemic of diabetes with its overwhelming burden on our healthcare system requires better therapeutic strategies. Here we present a promising novel approach for a curative strategy that may be accessible for all insulin-dependent diabetes patients. We designed a subcutaneous implantable bioartificial pancreas (BAP)—the "β-Air"—that is able to overcome critical challenges in current clinical islet transplantation protocols: adequate oxygen supply to the graft and protection of donor islets against the host immune system. The system consists of islets of Langerhans immobilized in an alginate hydrogel, a gas chamber, a gas permeable membrane, an external membrane, and a mechanical support. The minimally invasive implantable device, refueled with oxygen via subdermally implanted access ports, completely normalized diabetic indicators of glycemic control (blood glucose intravenous glucose tolerance test and HbA1c) in streptozotocin-induced diabetic rats for periods up to 6 months. The functionality of the device was dependent on oxygen supply to the device as the grafts failed when oxygen supply was ceased. In addition, we showed that the device is immunoprotective as it allowed for survival of not only isografts but also of allografts. Histological examination of the explanted devices demonstrated morphologically and functionally intact islets; the surrounding tissue was without signs of inflammation and showed visual evidence of vasculature at the site of implantation. Further increase in islets loading density will justify the translation of the system to clinical trials, opening up the potential for a novel approach in diabetes therapy.